Menjadi Korban yang Disalahkan dalam Novel Permata dalam Lumpur Karya Satria Nova dan Nur Huda - Eva Fauziyanti sutomo (KOMUNIDA : Media Komunikasi dan Dakwah, 2020)
Surabaya is the second largest city after Jakarta, as the second largest city, Surabaya is a densely populated area, can be found various kinds of informal economic activities that have existed since colonial times, ranging from street vendors to prostitution. Dolly is an exclusive area located in Surabaya. This region is tehe largest prostitution in Indonesia, even beating in Southeast Asia. Research on the Permata In the Mud novel by Satria Nova and Nur Huda focuses on the representation of the meaning of violence on prostitutes, to lead us to a thought that criticizes every form of violence against women. This research method is a qualitative analysis, using Ferdinand de Saussure's semiotic analysis, which looks at markers and markers. The data used in the form of texts that describe violence against prostitutes in the novel Permata Dalam Lumpur, which is read repeatedly. The results found several meanings of violence on prostitutes obtained from several chapters. The results showed that the Permata novel in the mud contained the meaning of violence on prostitutes. In this study also found that one commercial sex worker is a victim of a pimp. Keywords: Ferdinand de Saussure; novel; semiotics; violence against prostitutes